2017
DOI: 10.7567/jjap.56.06gg10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of controlled strain in silicon nanowire by UV Raman spectroscopy

Abstract: The evaluation of strain states in silicon nanowires (Si NWs) is important not only for the surrounding gate field-effect transistors but also for the thermoelectric Si NW devices to optimize their electric and thermoelectric performance characteristics. The strain states in Si NWs formed by different oxidation processes were evaluated by UV Raman spectroscopy. We confirmed that a higher tensile strain was induced by the partial presence of a tetraethyl orthosilicate (TEOS) SiO2 layer prior to the thermal oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…12) In particular, it has been reported that Raman spectroscopy is a powerful strain evaluation technique, because it has advantages such as a nondestructive measurement and a high spatial resolution. [13][14][15][16][17][18][19][20][21] To evaluate strain in Si 1−x Ge x by Raman spectroscopy quantitively, phonon deformation potentials (PDPs) are necessary for a conversion from a Raman wavenumber shift to a stress value. [22][23][24][25] PDPs indicate a relationship between strain tensor and force constant tensor.…”
Section: Introductionmentioning
confidence: 99%
“…12) In particular, it has been reported that Raman spectroscopy is a powerful strain evaluation technique, because it has advantages such as a nondestructive measurement and a high spatial resolution. [13][14][15][16][17][18][19][20][21] To evaluate strain in Si 1−x Ge x by Raman spectroscopy quantitively, phonon deformation potentials (PDPs) are necessary for a conversion from a Raman wavenumber shift to a stress value. [22][23][24][25] PDPs indicate a relationship between strain tensor and force constant tensor.…”
Section: Introductionmentioning
confidence: 99%
“…The wavelength of the excitation light source was 355 nm as in the dry Raman measurement, the NA of the water-immersion lens and refractive index n of water were 1.2 and 1.3, respectively. [22][23][24] Anisotropic biaxial stresses σ xx and σ yy were defined as the stress along the long axis and the short axis, respectively, and could be obtained with the use of the two optical phonon modes. 25) By substituting the wavenumber shifts from the strain-free Raman shift values ω 0 of the LO and TO phonon modes for Δω LO and Δω TO in Eq.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…( 1), σ xx and σ yy were obtained. 23,26) w w 30 1 Figure 5 shows Raman spectra of the Si substrate under the SiN patterns. A broad peak appeared around 480 cm −1 derived from a-Si for the samples with etching times of 35 and 40 s. On the other hand, this broad peak did not appear for the sample with an etching time of 45 s. Therefore, it is considered that there seems to be a correlation between the Raman spectrum of a-Si and etching time.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In this context, the surface properties of NWs assume a notably significant role and are regarded as pivotal factors that influence their mechanical attributes [12,16,17]. Furthermore, intrinsic effects such as the stresses generated in NWs during fabrication, assembly, and surface interactions are recognized as dominant parameters that have significant effects on the performance and properties of NWs [12,[18][19][20][21][22][23][24][25]. Nanomechanical modeling techniques are developed as a means to interpret the behavior of NWs at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%